2010
DOI: 10.1002/jsfa.3797
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in phenotypic and nutritional traits in vegetable amaranth (Amaranthus tricolor), a nutritionally underutilised crop

Abstract: Cluster analysis has proved to be an effective method in grouping strains that may facilitate effective management and utilisation in crop-breeding programmes. The diverse strains falling in different clusters were identified, which can be utilised in different hybridisation programmes to develop high-foliage-yielding varieties rich in nutritional components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 24 publications
8
53
0
Order By: Relevance
“…So, these traits should be paid attention in vegetable amaranth breeding programmes. The positive and significant correlations between yield and yield components in vegetable amaranth were also reported by Shukla and Singh (2002), Aruna et al, (2009), Shukla et al, (2010, Ahammed et al, (2012), Raja et al, (2012), Chattopadhyay et al, (2013), Mahabub et al, (2013), Hasan et al, (2013), Khurana et al, (2013), Dhangrah et al, (2015) and Gerrano et al, (2015). However, there was a nonsignificant negative correlation between yield and number of branches per plant (r= -0.262, -0.222, -0.123 at 30, 60 and 90 DAS respectively) and number of leaves per plant (r = -0.031, -0.122 at 60 and 90DAS respectively).…”
Section: Correlation Coefficient Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…So, these traits should be paid attention in vegetable amaranth breeding programmes. The positive and significant correlations between yield and yield components in vegetable amaranth were also reported by Shukla and Singh (2002), Aruna et al, (2009), Shukla et al, (2010, Ahammed et al, (2012), Raja et al, (2012), Chattopadhyay et al, (2013), Mahabub et al, (2013), Hasan et al, (2013), Khurana et al, (2013), Dhangrah et al, (2015) and Gerrano et al, (2015). However, there was a nonsignificant negative correlation between yield and number of branches per plant (r= -0.262, -0.222, -0.123 at 30, 60 and 90 DAS respectively) and number of leaves per plant (r = -0.031, -0.122 at 60 and 90DAS respectively).…”
Section: Correlation Coefficient Analysissupporting
confidence: 78%
“…and Chattopadhyay et al, (2013) for leaf/stem ratio, Hasan et al, (2013) and Chattopadhyay et al, (2013) for leaf length and leaf width, Shukla et al, (2010) and Khurana et al, (2013) for protein content. It was observed that carotenoids (0.189) exhibited positive and relatively low direct effect on foliage yield.…”
Section: Path Coefficient Analysismentioning
confidence: 99%
“…Amaranthus species also contains various volatiles and polyphenols, and has antioxidant, antimalarial, and antiviral properties, which prevent cancer, cardiovascular diseases, diabetes, etc. (Dasgupta & De, 2007;Jiang et al, 2011;Khandaker et al, 2008;Scalbert et al, 2005;Shukla et al, 2010). It was reported that amaranth contains protein, ascorbic acid, and mineral nutrients of Ca, Fe, Mg, P, K, and Na, which are considered as the nutritional value in vegetables (USDA, 1984).…”
Section: Glasshouse Experiment: Effects Of Soil Types On Amaranth 4 Lmentioning
confidence: 99%
“…The cost effectiveness of the production of amaranth leaves increases as the red color increases. Studies on A. tricolor showed that chlorophyll content and ascorbic acid are the major contributing traits of PC1 (Shukla et al, 2010). Chlorophyll content may affect foliage yield with the increment of photosynthetic rate by increasing the vegetative growth of amaranth (Shukla et al, 2006).…”
Section: Mean Plasticity Indexmentioning
confidence: 99%
“…) properties (Maharwal et al, 2005;Hilou et al, 2006;Roy et al, 2006). However, recent studies on the C4 photosynthetic pathway, wide genetic diversity and phenotypic plasticity of amaranth suggest the necessity to explore the influence of environmental factors on amaranth crop (Shukla et al, 2010).…”
mentioning
confidence: 99%